Banjar Traditional Performing Arts as Curriculum Development Study Materials Music Education at Lambung Mangkurat University - Sumasno Hadi (International Conference on Science, Education, and Technology, 2022)
The form of the arts education curriculum based on the culture of the community is the application of the contextual art education paradigm. In the current era, this paradigm is seen as relevant to be developed in Indonesia, especially in art education in universities. Focusing on the art education curriculum at the Program Studi Pendidikan Seni Pertunjukan Universitas Lambung Mangkurat (ULM), this study aims to explore the values ​​of education and local wisdom in the traditional performing arts of the Banjar people in South Kalimantan, especially in the type of traditional music. Through the hermeneutical-interpretative method, the analysis of this research focuses on three forms of Banjar traditional music, namely Panting Music, Madihin Performances, and Gamalan Banjar. Important data obtained through observation, interviews, and literature and document studies. Results Based on this research, it is known that the development of the undergraduate curriculum at the Program Studi Pendidikan Seni Pertunjukan ULM can refer to the traditional musical performing arts of the Banjar people in South Kalimantan. From this, the content of music that can be arranged as an aspect of the study of Panting Music, Madihin Performances, and Gamalan Banjar covers the main musical aspects, such as the organology of musical instruments, techniques of playing musical instruments/vocals, songs, and the form of presentation. The results of this study are seen to have benefits in the context of developing theories, educational models and learning materials that strengthen the vision and mission of the ULM institution.